Collaborative Active Learning Practical Activity-Based Approaches to Learning, Assessment and Feedback - Chang-Tik, Chan.; Kidman, Gillian; Tee, Meng Yew. (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
This book discusses activity-based collaborative active learning (CAL) approaches in connection with the learning and teaching of STEM and non-STEM disciplines. It also covers feedback and assessment activities as learning activities supported by learning technologies and applied in appropriate learning spaces. The contributing authors discuss in detail the implementation and facilitation of activity-based CAL strategies, the problems encountered and corresponding mitigation measures. In addition, all activities are developed in a blended mode, making them suitable for readers at any level of education who are interested in trying out CAL. Covering both STEM and non-STEM disciplines, this book offers comprehensive guidelines for lecturers who are interested in active learning. Chan Chang-Tik is a Senior Fellow, Higher Education Academy (SFHEA) and an Adjunct Senior Lecturer at Monash University Malaysia. His research interests are in the areas of collaborative learning in informal spaces, blended learning, educational technologies, and assessment and feedback for learning. He has more than 30 years of teaching experience from the secondary to the tertiary level. He has designed and conducted numerous online and face-to-face professional training programs for lecturers. He has more than five years of research experience and he has published a book chapter and numerous articles in peer-reviewed journals. Gillian Kidman is an Associate Professor at the Faculty of Education, Monash University, Australia. She is passionate about science and mathematics education. Her teaching and curriculum design in inquiry-based learning and teaching in the sciences is award winning. She has research interests in the integration of science and mathematics, especially the disciplinary and transdisciplinary thinking of STEM and STEAM. She is well respected throughout South East Asia, working extensively in STEM education with the South East Asian Ministries of Education, and the Regional Education Centre of Science and Mathematics (RECSAM) in Penang, Malaysia. Gillian is the co-editor for the International Journal of Geographical and Environmental Education (IRGEE) and is a member of the IGU CGE Steering Committee. Meng Yew Tee is a Senior Lecturer at the Faculty of Education, University of Malaya, Malaysia. His multidisciplinary academic and professional experience - in education, management, journalism, technology and psychology - cultivated his interest in researching construction of knowledge that cannot be learned merely through direct instruction. He also researches teachers' classroom practices, how people learn and construct knowledge, teaching and learning in collaborative settings as well as education systems. He has published numerous book chapters and articles in peer-reviewed journals.
Part 1: Theoretical Perspectives of Collaborative Active Learning -- Chapter 1: Introduction: Collaborative Active Learning - Strategies, Assessment and Feedback -- Chapter 2: Active Learning: An Integrative Review -- Chapter 3: Student Collaboration through Assessment, Feedback and Peer Instruction -- Part 2: Practical Activity-based Approaches in Different Disciplines -- Chapter 4: Learning to Teach with Technology with Real-world Problem-based Learning -- Chapter 5: Collaborative Learning in Informal Spaces: Formulating a Pedagogical Project of Student-Centred Active Learning in Gender Studies -- Chapter 6: Collaborative Active Learning (CAL) Approach in Finance: A Case of Business Strategy Pitch Presentation -- Chapter 7: Scavenger Hunt Activity to Reinforce Engineering Fundamentals -- Chapter 8: Future-proofing Healthcare Skills Education: Technology-enhanced Collaborative Learning and Peer Teaching Strategies for Large Student Cohorts in Anatomy Practicals -- Chapter 9: Online Collaborative Active Learning in Psychology -- Chapter 10: Implementing a Successful Collaborative Active Learning Approach in Information Technology Discipline -- Chapter 11: Using Team-based Scenario Learning (TBSL) Approach to Teach Audit Risk -- Chapter 12: Peer-led Case Study Methodology in the Learning of Statistics -- Part 3: Conceptual Framework and Pedagogical Perspectives -- Chapter 13: Conceptual Framework for Disciplinary Approaches to Collaborative Active Learning -- Chapter 14: Technologies and Learning Spaces for Collaborative Active Learning.
Keywords: Education-Research.; Learning, Psychology of; Educational Research; Learning Theory; Instructional Theory